Pear seedling production by double grafting in quince using ’Japonês’ as rootstock - Seifert, Karine Ester; Pio, Rafael; Celant, Viviane Marcela; Chagas, Edvan Alves (Pesquisa Agropecuaria Brasileira, 2010)
The objective of this work was to evaluate the viability of using 'Japonês' quince as rootstock for pear tree cultivars through intergrafting with other quince cultivars using the double-grafting process. 'Seleta' and 'Triunfo' pear trees were grafted by budding and cleft grafting onto 15-cm clefts of 'Portugal', 'Provence', 'Mendoza Inta-37' and 'Smyrna de Harcy' quince trees. The grafted clafts were stored in a cold chamber (4ºC) for 24 hours, and were then grafted onto 'Japonês' roostocks by full-rift cleft grafting. A completely randomized design with 2x2x4 factorial arrangement was used. After 60 and 120 days, the percentage of sprouting, diameter, the medium length and the dry mass of the grafts and intergrafts were evaluated. No double or triple interaction between the studied factors was detected, only differences among isolated factors. Differences in sprouting percentage were detected only between the grafting methods and the quince cultivars used as intergrafts. Double-grafting is viable for pear seedling production using 'Japonês' rootstocks intergrafted with Cydonia quince trees.